A comparative study of help-seeking behavior in an urban community. - Cruz, Erlinda B.
People have varied ways of medical help-seeking. Some subscribe only to medical health workers while others utilize both the indigenous and professional health practitioners. The same clients may secure preventive care and early treatment of illness conditions or practice informal consultations and seek treatment only when the illness has become severe. Several factors account for these variables in medical help-seeking.